O luxo na hotelaria no Brasil: panoramas e a atuação da associação Relais & Châteaux - Barbosa, Iury Eduardo Lobato (Universidade Federal de São Carlos, 2023)
This master's dissertation examines the role of the Relais & Châteaux association in the current Brazilian luxury tourism market. The analysis focuses on the interplay between the location and operation of hotels affiliated with this association and the Brazilian regional context. The objective is to comprehend the influence of luxury hotels in Brazil and evaluate the concept of luxury within these ventures, considering geographical factors in their locations. The study adopts a qualitative approach, grounded in a literature review to establish the theoretical foundation and guide the research, as well as an analysis of secondary sources from entities related to Luxury Tourism, both in Brazil and internationally. The data analysis follows the perspective of historical-dialectical materialism, critically interpreting the data and reflecting on the empirical reality, allowing a comprehensive and in-depth understanding of luxury hospitality in the Brazilian context. It becomes evident that Brazil holds a peripheral position in the global luxury hotel landscape, even with the current influx of international capital through the establishment of new hotel ventures. Furthermore, luxury hotels in Brazil are predominantly concentrated in coastal areas, reinforcing the national identity oriented towards Beach and Sun Tourism and in prominent financial districts, reflecting the influence of capital in shaping regions of higher centrality in spatial production. Additionally, the significant role of independent hotel associations is highlighted in positioning their members in the global landscape of luxury establishments, expanding the visibility of these ventures beyond the regional scope.
The luxury in the hotel industry in Brazil: scenarios and the role of the Relais & Châteaux association
Keywords: Geografia do Turismo; Turismo de luxo; Consumo; Hotelaria de luxo; Relais & Châteaux; Tourism geography; Luxury tourism; Consumption; Luxury hospitality; CIENCIAS HUMANAS::GEOGRAFIA